Analisis Pengaruh Pinjaman Luar Negeri, IPM, dan Inflasi terhadap Pertumbuhan Ekonomi di Indonesia - Muhammad Nauval Fadhil (Jurnal Indonesia Sosial Teknologi, 2026)
Economic growth is a key indicator of national development and is influenced by macroeconomic and socioeconomic factors. This study examines the effects of foreign loans, the Human Development Index (HDI), and inflation on Indonesia’s economic growth using annual secondary data from 1993–2023, comprising 31 observations. The data were obtained from Statistics Indonesia (BPS), Bank Indonesia, and the World Bank. A quantitative explanatory approach was employed using Ordinary Least Squares (OLS) multiple linear regression. Model adequacy was evaluated through classical assumption tests, while hypothesis testing was conducted using t-tests, F-tests, and the coefficient of determination (R²). The findings show that foreign loans have a positive and statistically significant effect on economic growth (p < 0.05), indicating that productive external borrowing supports investment and development. HDI also has a positive and significant influence (p < 0.05), demonstrating that improvements in education, health, and living standards contribute to sustainable economic expansion. Conversely, inflation does not significantly affect economic growth (p > 0.05) during the observation period, although price stability remains essential for maintaining macroeconomic resilience. The model explains a substantial proportion of the variation in economic growth, as reflected by the R² value. However, the presence of autocorrelation indicates a limitation of the OLS model and suggests that future research should apply more robust time-series techniques to obtain more reliable estimates. These findings imply that the government should prioritize the productive allocation of foreign loans, strengthen investment in human capital, and maintain prudent monetary policies to achieve sustainable and inclusive economic growth.